2019
DOI: 10.1166/asem.2019.2448
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Characterization of Copper Nanoparticles Using a Bioflocculant Extracted from Alcaligenis faecalis HCB2

Abstract: Bioflocculant from Alcaligenis faecalis HCB2 was used in the eco-friendly synthesis of the copper nanoparticles. Nanoparticles were characterized using a scanning electron microscope (SEM), transmission electron microscopy (TEM), UV-visible spectroscopy, thermo gravimetric analysis (TGA) and Fourier Transform Infrared Spectroscopy (FT-IR). The transmission electron microscopy images showed close to spherical shapes with an average particle size of ∼53 nm. Energy-dispersive X-ray spectroscopy analysis confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 0 publications
2
20
0
1
Order By: Relevance
“…The EDX results showed the presence of oxygen, carbon, phosphorus, chlorine, potassium, and sulfur elements in the purified bioflocculant. The presence of oxygen, copper, phosphorus, magnesium, calcium, chlorine, and sulfur elements in the assynthesized nanoparticles represented the passivation of the copper nanoparticles with the bioflocculant [51]. The EDX results confirmed the presence of Cu in a sample which was an indication that the bioflocculant could be used as a capping agent in CuNPs biotransformation.…”
Section: Edxmentioning
confidence: 75%
See 1 more Smart Citation
“…The EDX results showed the presence of oxygen, carbon, phosphorus, chlorine, potassium, and sulfur elements in the purified bioflocculant. The presence of oxygen, copper, phosphorus, magnesium, calcium, chlorine, and sulfur elements in the assynthesized nanoparticles represented the passivation of the copper nanoparticles with the bioflocculant [51]. The EDX results confirmed the presence of Cu in a sample which was an indication that the bioflocculant could be used as a capping agent in CuNPs biotransformation.…”
Section: Edxmentioning
confidence: 75%
“…From the study of Dlamini et al [51], the obtained TEM image showed that as-synthesized copper nanoparticles, using a bioflocculant extracted from Alcaligenes faecalis HCB2, were close to the spherical shape. The copper nanoparticles appeared to be close to spherical in shape and aggregation [51].…”
Section: Transmission Electron Microscope (Tem)mentioning
confidence: 99%
“…Three phases were noticed in the thermogravimetric analysis of as-synthesized copper nanoparticles. The first phase is observed from 40–120 °C due to the loss of moisture, the second phase appeared around 150–200 °C and could be attributed to the decomposition of polymer, and the third phase was observed at higher temperatures due to more weight loss from the samples [15]. The UV-Visible spectra of the bioflocculant and as-synthesized copper nanoparticles showed peak maxima at around 290–300 nm that could be ascribed to Cu nanoparticles formation [15].…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of copper nanoparticles was monitored through physical observation and characterization. Control was a copper sulphate solution without bioflocculant [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation